214k views
2 votes
Err i dont know U>U here you go peeps

Err i dont know U>U here you go peeps-example-1
User Moghya
by
4.9k points

1 Answer

7 votes

Answer:


{x}^(2) + {y}^(2) + 4x - 2y = - 1 \\ ( {x}^(2)+2*2* x + {2}^(2) ) - 4 + ({y}^(2) - 2 * 1 * y + {1}^(2) ) - 1 = - 1 \\ {(x + 2)}^(2) - 4 + {(y - 1)}^(2) - 1 = - 1 \\ {(x + 2)}^(2) + {(y - 1)}^(2) = 4\\ {(x + 2)}^(2) + {(y - 1)}^(2) = {( 2) }^(2)

Therefore, the centre of the circle is in ( -2, 1 )

and the radius of the circle is 2.

Formula used :-----


{(x - a)}^(2) + {(y - b)}^(2) = {r}^(2)

equation of the circle

where r is the radius of the circle.

(A) 2 is the right answer.

User Ssh Quack
by
4.8k points